INTEGRATION OF LIFE SKILLS TRAINING IN THE DEAF CURRICULUM: CAN IT DEVELOP CHILDREN'S SOCIAL SKILLS? - Varary Mechwafanitiara Cantika; Rusman Rusman (Graduate School of Universitas Negeri Malang, 2023)
This study aims to describe the importance of integrating life skills in developing the social skills of deaf children. The method used in this study was case study. The research subject in this study was two students and two teachers. Research instruments in this study used questionnaires. The instrument's preparation used a simple modification of the Social Skills Rating System (SSRS) measurement and then tested its validity using content validity, namely expert judgment. Data analysis in this study used descriptive qualitative, which was carried out by accumulating respondents' answers and adjusting to social skills criteria in the SSRS measurement. The results of this study indicate that integrating life skills programs into the curriculum can develop the social skills of deaf children. These social skills are shown in interactions with peers, which include cooperative behavior, assertiveness, and empathy.Penelitian ini bertujuan untuk mendeskripsikan pentingnya mengintegrasikan kecakapan hidup dalam mengembangkan keterampilan sosial anak tunarungu. Metode yang digunakan dalam penelitian ini adalah studi kasus. Subyek penelitian dalam penelitian ini adalah dua siswa dan dua guru. Instrumen dalam penelitian ini menggunakan kuesioner. Penyusunan instrumen menggunakan modifikasi sederhana pengukuran Social Skills Rating System (SSRS) kemudian diuji validitasnya menggunakan validitas isi yaitu expert judgment. Analisis data dalam penelitian ini menggunakan deskriptif kualitatif yang dilakukan dengan cara mengakumulasikan jawaban responden dan disesuaikan dengan kriteria keterampilan sosial dalam pengukuran SSRS. Hasil penelitian ini menunjukkan bahwa pengintegrasian program kecakapan hidup ke dalam kurikulum dapat mengembangkan keterampilan sosial anak tunarungu. Keterampilan sosial ini ditunjukkan dalam interaksi dengan teman sebaya, yang meliputi perilaku kooperatif, ketegasan, dan empati.